2019
DOI: 10.4236/ajps.2019.101017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organisation Influences Citrus <i>Pseudocercospora</i> Leaf and Fruit Spot Disease Severity in Cocoa-Based Agroforestry Systems

Abstract: An investigation to assess the spatial structure and severity of Pseudocercospora leaf and fruit spot disease (PLFSD) on citrus trees in cocoa-based agroforests was carried out in three contrasting ecological zones in southern Cameroon, viz: 1) the humid forest zone, 2) the degraded forest zone, and 3) the forest-savannah transition zone. Two main parameters were investigated viz: 1) the spatial structure of cocoa based agroforests, and 2) the disease severity. In total, the spatial structure of 19 cocoa-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Plots with a regular spatial structure were less affected by PFRD and those with an aggregated and random spatial structure were much more affected. Similar results were obtained by (Ndo et al 2019c). (Brown 2004) have suggested that aggregation of host populations enhances pathogen dispersal while regularity decreases it.…”
Section: Spatial Structure and Pfrd Intensitysupporting
confidence: 90%
See 1 more Smart Citation
“…Plots with a regular spatial structure were less affected by PFRD and those with an aggregated and random spatial structure were much more affected. Similar results were obtained by (Ndo et al 2019c). (Brown 2004) have suggested that aggregation of host populations enhances pathogen dispersal while regularity decreases it.…”
Section: Spatial Structure and Pfrd Intensitysupporting
confidence: 90%
“…Three main mechanisms illustrate the links between plant composition and the action of pests and diseases via resource variations. These are the mechanism of resource depletion for the pest, resource introduction for the pest, and resource introduction for a natural enemy or vector of the pest (Ngo Bieng et al 2017; Ndo et al 2019c).…”
Section: Introductionmentioning
confidence: 99%